Respuesta :

Answer:  k = -9

Step-by-step explanation:

kx² - 12x - 4 = 0

In order to have exactly one solution, it must be a perfect square.

Assume k is negative and factor out a negative 1.

-1(kx² + 12x + 4) = 0

[tex]\bigg(\sqrt{kx^2}+\sqrt4\bigg)^2=0\\\\[/tex]

The middle term = 12x [tex]= 2(\sqrt{kx^2})(\sqrt4)[/tex]

                               12x = 4x√k

                                3   = √k

                                9 = k

                                   

-1(9x² + 12x + 4) = 0

-9x² - 12x - 4 = 0

k=-9